Control interno a la gestión administrativa-financiera de la Compañía Imporellana SA., AÑO 2019 - Romero Macas, María Verónica (2021)
Nowadays it is of vital importance to have a technical internal control system that allows companies the correct use of their resources, safeguard their assets and obtain the expected financial returns. The objective of this project is to evaluate the impact of internal control on the administrative-financial management of the company Imporellana SA, to improve internal control processes in all areas of the company, by optimizing human, material, and economic resources and financial. Through internal control, rules and procedures are established to follow aimed at achieving institutional objectives, through adequate planning, organization and direction by senior managers with the collaboration of all those involved in the company. An exploratory study will be applied to have a clear vision of the current situation in which the company finds itself and to be able to detect the topics of interest that lead us to the objectives set. Through a descriptive investigation, it is intended to know the company, its nature and most important characteristics, using observation techniques, surveys and questionnaires applied to all collaborators, who will provide us with pertinent and relevant information to develop the investigation processes. Starting from the idea that there are deficiencies in internal control, to verify this premise, COSO 2013 will be applied, carrying out a logical and coherent analysis with the scientific concepts that we have on the research topic. Study in depth each component of internal control, its characteristics and properties implicit in each one, as well as its effect on the financial administrative management of the company. The aim of this research is to issue recommendations that help the company to improve its internal control strategies, minimize errors, avoid possible fraud, obtain better financial returns, expand in the market and allow job opportunities that merit in these difficult times. Keywords: Internal control, resources, planning, financial returns